Work-Related Perks Stimulation and Corporate R&D Investment in Chinese Listed Companies of Emerging Market - Jiang, Tao; Liao, Xinxin; Liu, Jun (American Journal of Management, 2020)
Based on the high risk and uncertainty of innovative behaviors, this paper studies the role and effect of work-related perks in the contract that encourages executives to respond to innovation in Chinese listed companies. From the manager risk-taking perspective, empirical testing with all A-share listed companies in P. R. China from 2007 to 2012 in fast-growing market found that under the control of monetary compensation and equity incentives, work-related perks promote an incentive and synergistic effect on corporate innovation; but the above effects are mainly observed in emerging high-tech companies that are strongly relied on corporate innovations. Therefore, the above results are not affected by differences in corporate governance, and may eliminate the opportunism behaviors of executives while managing the enterprise's innovative activities. The presented model could possibly be found useful to formulate and motivate executives to invest in innovation and minimize the embezzlement in fast-growing companies in emerging market.